The Effect of Training on Access Employment of Pre-Employment Card Participants - Awinda, Siti Nur Arliya; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to determine the effect of pre-employment card training at the Cybers Academy Institute in increasing a person's chances of getting access to employment. By using primary data, namely online surveys given to alumni of Cybers Academy training participants. The results of logistic regression analysis show that participants who take training at Cybers Academy have a greater tendency to get access to employment. Furthermore, in the age group, age 26 years and over has an influence on job access. Participants who have previous work experience and attended training at Cybers Academy have a greater chance of gaining access to employment. Meanwhile, participants who live in the city and attend training have a greater chance of finding job access. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan kartu pra kerja di Cybers Academy Institute dalam meningkatkan peluang seseorang mendapatkan akses pekerjaan. Dengan menggunakan data primer yaitu survei online yang diberikan kepada alumni peserta pelatihan Cybers Academy. Hasil analisis regresi logistik menunjukkan bahwa peserta yang mengikuti pelatihan di Cybers Academy memiliki kecenderungan lebih besar untuk mendapatkan akses pekerjaan. Selanjutnya pada kelompok umur, umur 26 tahun ke atas mempunyai pengaruh terhadap akses kerja. Peserta yang memiliki pengalaman kerja sebelumnya dan mengikuti pelatihan di Cybers Academy memiliki peluang lebih besar untuk mendapatkan akses pekerjaan. Sedangkan peserta yang berdomisili di kota dan mengikuti pelatihan mempunyai peluang lebih besar untuk mendapatkan akses pekerjaan.